Case-law of the European Court of Human Rights and the European Union Law: An Area of Important Interaction and Dialogue for Stronger Human Rights Protection in Europe - Pavlo Pushkar (Наукові записки НаУКМА: Юридичні науки, 2020)
An overlap in the activities of the Council of Europe and the EU as regards the protection of human rights leads to cross-fertilisation of both systems. Commitment to human rights and the Convention is notably manifested in the on-going dialogue on accession of the EU to the European Convention on Human Rights. Ideally, interaction between the Council of Europe and the European Union should lead to construction of a uniform human rights constitutional legal space, built on the same principles of compliance with the rule of law and human rights, a destination that still remains on the horizon. The process of execution of judgments of the Strasbourg Court, which is a forward looking technical and non-political process, with potential political consequences, results in the transformation of the legal systems of the Council of Europe member states and thus assists them in bringing their legal systems closer to being compatible with the EU accession process. Thus, the strategic aim of the European integration and EU accession should be aligned with the Strasbourg judgment’s implementation process, success in execution of judgments equalling to success in attainment of the Copenhagen accession criteria.